Comparative hygienic risk assessment of groundwater contamination by herbicides of different chemical classes and hazard prediction for human after consumption of contaminated water = Порівняльна гігієнічна оцінка ризику забруднення підземних вод гербіцидами різних класів та прогноз небезпеки для людини при споживанні забрудненої води. - Antonenko, A. M.; Vavrinevych, O. P.; Omelchuk, S. T.; Korshun, M. M. (Journal of Education, Health and Sport, 2016)
Antonenko A. M., Vavrinevych O. P., Omelchuk S. T., Korshun M. M. Comparative hygienic risk assessment of groundwater contamination by herbicides of different chemical classes and hazard prediction for human after consumption of contaminated water = Порівняльна гігієнічна оцінка ризику забруднення підземних вод гербіцидами різних класів та прогноз небезпеки для людини при споживанні забрудненої води. Journal of Education, Health and Sport. 2016;6(9):873-882. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.161844 http://ojs.ukw.edu.pl/index.php/johs/article/view/3942 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.09.2016. УДК 613:632.954:633.15 COMPARATIVE HYGIENIC RISK ASSESSMENT OF GROUNDWATER CONTAMINATION BY HERBICIDES OF DIFFERENT CHEMICAL CLASSES AND HAZARD PREDICTION FOR HUMAN AFTER CONSUMPTION OF CONTAMINATED WATER A. M. Antonenko, O. P. Vavrinevych, S. T. Omelchuk, M. M. Korshun O.O. Bogomolets National medical university Department of hygiene and ecology Abstract In the structure of main groundwater pollutants leading position is occupied by chemical pesticides. Herbicides are among the most widely used classes of pesticides, according to application technology introduced directly into the soil. Migrating on the soil profile, they create a danger of groundwater contamination that requires their constant control and monitoring. Objective – comparative evaluation of risk of adverse effects on human health by drinking of water contaminated with the most common herbicides. We have studied representatives of herbicides extensively used in agriculture: chloroacetamides; sulfonil-carbonyl-triazolinone, oxazoles, triketones, sulfonylurea, phosphonoglycine. Prediction of migration opportunities in groundwater of studied herbicides was carried out by GUS – Groundwater Ubiquity Score. For determination of potential risk to human health by drinking of water containing pesticides screening model of maximum concentration of pesticide in groundwater determination (SCI-GROW) was used. For the evaluation of the parameters of SCI-GROW a method of comprehensive assessment developed by us has been used. It is based on establishing of maximum possible daily intake of pesticide with water and subsequently comparing with acceptable daily intake of pesticide with water. It was established that in soil and climatic conditions of Ukraine for most of the test substances probability of leaching into groundwater is negligible; in conditions of other European countries – risk of leaching is low. Maximum possible concentration of the test herbicides in groundwater are insignificant and are much lower of acceptable, which is associated primarily with low application rates and indicates relative safety for human health intakes such water. Key words: groundwater, herbicides, risk, maximal concentration, allowable intake. ПОРІВНЯЛЬНА ГІГІЄНІЧНА ОЦІНКА РИЗИКУ ЗАБРУДНЕННЯ ПІДЗЕМНИХ ВОД ГЕРБІЦИДАМИ РІЗНИХ КЛАСІВ ТА ПРОГНОЗ НЕБЕЗПЕКИ ДЛЯ ЛЮДИНИ ПРИ СПОЖИВАННІ ЗАБРУДНЕНОЇ ВОДИ А. М. Антонечко, О. П. Вавріневич, C. Т. Омельчук, М. М. Коршун Національний медичний університет імені О.О. Богомольця Кафедра гігієни та екології У статті представлені порівняльні результати гігієнічної оцінки ризику забруднення підземних вод гербіцидами різних хімічних класів і прогнозування небезпеки для людини при вживанні забрудненої води; надані рекомендації щодо застосування таких гербіцидів Ключові слова: ґрунтові води, гербіциди, ризик, максимальна концентрація, допустиме надходження.